Ultrasound imaging of the appendix testis and appendix epididymis - Johnson, K.A.; Dewbury, K.C. (Clinical radiology, 1996)
The appendix testis and epididymis are well visualized on ultrasound examination. It is important to recognize the normal anatomy of the appendages to exclude them as a cause of pathology and confirm their presence as normal structures. We describe the appearances of the appendices testis and epididymis in fifty-one consecutive patients presenting to the Southampton Radiology Department. The appendix testis was identified on 80% of testes examined by ultrasound and the appendix epdidymis on 6% of testes.